1994
DOI: 10.1038/eye.1994.130
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of back scattering in the nuclear area of the non-cataractous human lens

Abstract: SUMMARYThe spatial distribution of back scattering from a vertical cross-section of the nuclear area in non-cataractous human lens was investigated. The cross-section was centred on the pupil. There is no significant difference in Scheimpflug photography has proved to be an important tool for quantitative measurements of lens nuclear transparency,l-1O Nuclear cataract develops symmetrically around the anterior-posterior axis, I I Therefore, one Scheimpflug photographic section is sufficient to represent the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…A primary analysis of the precision of the measurement method17 21 demonstrated that the variability between eyes of an individual, among photographs within an eye, and measurements within photograph is negligible compared with the variation from one occasion to another within an individual. Therefore, only one eye in each individual, one photograph from each eye, and one measurement of each photograph was considered.…”
Section: Methodsmentioning
confidence: 99%
“…A primary analysis of the precision of the measurement method17 21 demonstrated that the variability between eyes of an individual, among photographs within an eye, and measurements within photograph is negligible compared with the variation from one occasion to another within an individual. Therefore, only one eye in each individual, one photograph from each eye, and one measurement of each photograph was considered.…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that backscattered light from the nuclei of noncataractous lenses decreases as one moves away from the lens axis. 15 This suggests a very simple model of a nuclear cataract. Assume a spherically symmetrical distribution of protein aggregates such that backscattered light decreases from a maximum at the center to a minimum at a distance of 1 mm from the center.…”
Section: Figmentioning
confidence: 98%
“…Die Zunahme der Lichtstreuung in den einzelnen Zonen der Linse verläuft dabei zeitlich gesehen ab dem adulten Stadium recht gleichmäûig [46]. Auch beim alten Menschen bleibt in der Linse eine solche Profilierung der Lichtstreuung zwischen Rinde und Kern erhalten [41], vorausgesetzt es kommt zu keiner pathologischen Verdichtung durch äuûere oder innere, chemische oder physikalische Kataraktnoxen. Die senile Kernverdichtung stellt dabei bereits eine pathologische Zunahme der Lichtstreuung dar, die klinisch oft mit dem Sammelbegriff (prä-)senile Katarakt belegt wird [44].…”
Section: Normale Altersveränderungen In Hornhaut Und Linseunclassified